1997
DOI: 10.1007/s004010050735
|View full text |Cite
|
Sign up to set email alerts
|

Lack of correlation between plaque burden and cognition in the aged monkey

Abstract: To assess whether amyloid plaque accumulation in the monkey brain can account for age-related cognitive impairment that begins at about 20 years of age, we measured plaque content in the brains of 14 rhesus monkeys aged 5-30 years. We used immunohistochemistry employing the monoclonal antibody 6E10, which is specific to amino acids 1-17 of the amyloid beta peptide to identify amyloid plaques in serial coronal sections of the forebrain. Amyloid plaques accumulate with age, starting at 25 years of age and escala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(56 citation statements)
references
References 44 publications
3
53
0
Order By: Relevance
“…One recent study found progressively greater impairments across subjects from 30 to 90 years of age (Davis et al, 2003), whereas another reported a steady decrease across multiple measures of memory in healthy adults from age 20 forward (Park et al, 2003). Declines in memory from young adulthood to middle age have also been described previously for rats (Deupree et al, 1993;Granger et al, 1996;Oler and Markus, 1998;Ward et al, 1999;Meneses et al, 2004) and monkeys (Herndon et al, 1997;Sloane et al, 1997), suggesting that this effect could be a general feature of mammalian brain. These observations raise the question of whether long-term potentiation (LTP), a form of synaptic plasticity widely regarded as a substrate of memory encoding, also begins to deteriorate relatively early in adult life.…”
Section: Introductionmentioning
confidence: 54%
“…One recent study found progressively greater impairments across subjects from 30 to 90 years of age (Davis et al, 2003), whereas another reported a steady decrease across multiple measures of memory in healthy adults from age 20 forward (Park et al, 2003). Declines in memory from young adulthood to middle age have also been described previously for rats (Deupree et al, 1993;Granger et al, 1996;Oler and Markus, 1998;Ward et al, 1999;Meneses et al, 2004) and monkeys (Herndon et al, 1997;Sloane et al, 1997), suggesting that this effect could be a general feature of mammalian brain. These observations raise the question of whether long-term potentiation (LTP), a form of synaptic plasticity widely regarded as a substrate of memory encoding, also begins to deteriorate relatively early in adult life.…”
Section: Introductionmentioning
confidence: 54%
“…Although amyloid plaques are frequently observed, in contrast to Alzheimer's disease, the ratio of amyloid β peptide 40 and 42 in the aged monkeys favors the shorter, less pathogenic form (Gearing et al 1996). While the accumulation of amyloid β plaques increases after age 25 in rhesus monkeys, the plaque content does not correlate with cognitive dysfunction, as measured by a standardized score derived from DNMS, spatial/color DRST, and spatial/object RL (Sloane et al 1997). The number of amyloid β plaques also fails to correlate with DR performance (Cork 1993).…”
Section: Plaques and Tanglesmentioning
confidence: 96%
“…In addition, the amyloid plaques that do accumulate do not show the distribution typical of AD or evidence of a predilection for the hippocampus and entorhinal cortex (Heilbroner and Kemper 1990). Additionally, there is no relationship between the accumulation of amyloid plaques and cognitive impairments (Sloane et al 1997). Finally, neurofibrillary tangles are a second critical and diagnostic feature of AD that is particularly related to the death of neurons but there is no clear evidence that neurofibrillary tangles are ever present in the rhesus monkey brain (Kimura et al 2003;and Finch and Austad, this publication).…”
Section: The Non-human Primate As a Model Of Normative Agingmentioning
confidence: 99%